(untitled) (Intent Research Scientific Journal, 2023)
In this article, the researcher presented her opinion on the need, relevance and importance of the economic analysis of econometric models. The choice of factors in creating econometric models, the resulting and influencing factors were also discussed. The main groups of models used in the forecasting and analysis of economic systems are shown.